2008
DOI: 10.1016/j.brainres.2008.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Unique responses of midbrain CART neurons in macaques to ovarian steroids

Abstract: CART (cocaine and amphetamine regulated transcript) is a neuropeptide involved in the control of several physiological processes, such as response to psychostimulants, food intake, depressive diseases and neuroprotection. It is robustly expressed in the brain, mainly in regions that control emotional and stress responses and it is regulated by estrogen in the hypothalamus. There is a distinct population of CART neurons located in the vicinity of the Edinger-Westphal nucleus of the midbrain that also colocalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
2
9
1
Order By: Relevance
“…The midbrain UCN1 cell bodies in macaques are located adjacent to the Edinger-Westphal nucleus, in an area referred to as the SOA [39]. These neurons also express cocaine and amphetamine regulated transcript or CART [25,58]. There were more detectable UCN1-positive neurons in the SS groups than in the HSR groups, which is the inverse of the fiber density.…”
Section: Discussionmentioning
confidence: 99%
“…The midbrain UCN1 cell bodies in macaques are located adjacent to the Edinger-Westphal nucleus, in an area referred to as the SOA [39]. These neurons also express cocaine and amphetamine regulated transcript or CART [25,58]. There were more detectable UCN1-positive neurons in the SS groups than in the HSR groups, which is the inverse of the fiber density.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine-and amphetamine regulated transcript (CART), discovered initially by Douglass et al via differential display RT-PCR analysis of brains of rats administered cocaine [10], is expressed mainly in central nervous system or neuronal origin cells [11], which is involved in a wide range of behaviors, such as regulation of food intake, energy homeostasis, and reproduction [12][13][14][15]. CART, as a potent anorectic peptide in hypothalamus, is regulated by leptin [16].…”
Section: Introductionmentioning
confidence: 99%
“…The developmental expression profile of cocaine- and amphetamine- regulated transcript (CART), a peptide that strongly but not completely co-localizes with Ucn 1 in the perioculomotor area (pIII) (Kozicz, 2003; Lazar et al, 2004; Lima et al, 2008; Xu et al, 2009), has been examined prenatally (Brischoux et al, 2002). It was reported that CART is expressed during early embryonic development, and the finding that these cells migrate through the ventral tegmentum area and settle in the pIII, has led to the argument that CART may be one of the earliest neuropeptides with a neuromodulatory role that is expressed in the brain (Brischoux et al, 2002; Risold et al, 2006).…”
Section: Introductionmentioning
confidence: 99%